2022
DOI: 10.3390/diagnostics12030770
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Adverse Post-Infarction Left Ventricular Remodeling Using a Multivariate Regression Model

Abstract: Background. In order to provide personalized medicine and improve cardiovascular outcomes, a method for predicting adverse left ventricular remodeling (ALVR) after ST-segment elevation myocardial infarction (STEMI) is needed. Methods. A total of 125 STEMI patients, mean age 51.2 (95% CI 49.6; 52.7) years were prospectively enrolled. The clinical, laboratory, and instrumental examinations were performed between the 7th and 9th day, and after 24 and 48 weeks, including plasma analysis of brain natriuretic peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Left ventricular remodelling is characterized by a sum of genetic, molecular, cellular and interstitial changes with subsequent alterations in cardiac size, shape and function after myocardial injury such as an ischemic event 20 . A recent study demonstrated that the development of adverse LV remodelling post myocardial infarction is related with an 8.5‐fold increase in the risk of cardiovascular events during a 48‐week follow‐up period 21 . Conversely, even minor reductions in LV remodelling can be associated with a decreased risk of heart failure and cardiovascular death 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Left ventricular remodelling is characterized by a sum of genetic, molecular, cellular and interstitial changes with subsequent alterations in cardiac size, shape and function after myocardial injury such as an ischemic event 20 . A recent study demonstrated that the development of adverse LV remodelling post myocardial infarction is related with an 8.5‐fold increase in the risk of cardiovascular events during a 48‐week follow‐up period 21 . Conversely, even minor reductions in LV remodelling can be associated with a decreased risk of heart failure and cardiovascular death 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Oleynikov et al have showed the predictive value of LV‐arterial coupling, defined as the ratio of arterial elastance to LV end‐systolic elastance, in the development of adverse LV remodelling (relative risk = 1.96, 95% CI: 1.11–3.46, p = .020) 21 . However, a recently published study demonstrated that PWV/GLS ratio was importantly associated with cardiovascular factors regardless of age and thus should preferably be used to assess ventricular‐arterial interaction over other traditional echocardiography‐derived markers 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Objective assessment of hemodynamic conditions is fundamental to guide the clinical management of the cardiac surgery patient during the postoperative period [ 1 , 2 , 3 ]. Meticulous fluid management is crucial in patients undergoing cardiac surgery, particularly in those with heart failure; prolonged operative and aortic cross-clamp time; or preexisting kidney, lung, or liver dysfunction [ 4 , 5 ]. Recent studies suggested that abdominal congestion can lead to or worsen renal and hepatic dysfunction and thus increase the risk of postoperative complications and lead to higher resource utilization [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%